ANALISIS DRPs STATIN DAN ESTIMASI RISIKO ATHEROSCLEROTIC CARDIOVASCULAR DISEASE (ASCVD) PASIEN DIABETES MELITUS TIPE 2 RAWAT JALAN DI RS “X” SAMARINDA - Irham Bakhtiar, Muh.; Novy Yudhistirawati; Hamzah, Hasyrul (Universitas Imelda Medan, 2023)
Atherosclerotic Cardiovascular Disease (ASCVD) is the main cause of death in patients with diabetes mellitus with a cardiovascular risk that will increase 2-4 times higher than non-diabetic patients. The statin group is a class of drugs recommended by ACC/AHA 2018 in reducing cardiovascular risk in patients with type 2 diabetes mellitus. This study aims to analyze Drug Related Problems (DRPs) of statin drugs in patients with type 2 diabetes mellitus and calculate the estimated risk for the next 10 years. The research was conducted using a non-experimental descriptive analytic method. Data collection was carried out retrospectively through a population of 194 type 2 diabetes mellitus patients at